THE HUI MUSLIM AND ISLAMIC JOURNALISM DURING THE REPUBLIC OF CHINA - Mai , Jianjun (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2025)
This study investigates the emergence and development of Islamic journalism among the Hui Muslim community during the Republican era in China (1912–1949). It addresses the research problem of how Hui Muslims used media as a religious strategy in response to modernity, nationalism, and identity challenges. The objective is to reconceptualize Hui journalism not as secular ethnic expression but as a purposeful Islamic project rooted in daʿwah and revivalism. Using a qualitative methodology based on historical and textual analysis of key publications—especially Yue Hua (The Moon Light)—the article identifies four interrelated dimensions of consciousness: religious, political, technological, and transnational ummatic. The findings reveal how Hui reformers strategically employed print media to assert Islamic identity, engage with nationalism, and connect with global Muslim movements. This study contributes to Islamic and media studies by restoring Hui Muslims’ religious agency and re-situating their journalistic activities within the broader context of 20th-century Islamic revivalism and minority religious media.